Uncertainty of Artificial Intelligence Assistant: The Effect of Assistant Type on Variety Seeking - Zhang, Yu; Yang, Mengya; Zhang, Ziling (Frontiers in Psychology, 2022)
AI voice assistants and self-service technologies have become popular in service marketing. As a result, it is essential to enrich the understanding of whether customers react differently to AI service context in comparison with human. This paper examines the effect of assistant type (AI vs. human) on consumers’ decision-making. Through three experiments, this research finds that variety-seeking will be higher when consumers are making decision in AI (vs. human) service environment. Furthermore, we test uncertainty as the underlying mechanism. Moreover, we demonstrate that this pattern is moderated by situational involvement. Specifically, in consumption contexts of high involvement, the consumers are less likely to seek variety, and in consumption contexts of low involvement, they prefer more variety. This research offers service providers new insights by revealing how, why, and when the interaction of AI technology influences consumers’ decision-making in service marketing.